Clinical Profile of Constipation in Children Under 5 Years of Age in Dr. Soetomo General Academic Hospital, Indonesia - Steven Christian Susianto; Vina Lidya Setjaputra; Alpha Fardah Athiyyah; Khadijah Rizky Sumitro; Andy Darma; Reza Gunadi Ranuh; Subijanto Marto Sudarmo (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Background: Childhood constipation is still common among children under 5 years of age. This study was conducted to determine the clinical profile of childhood constipation under 5 years of age at dr. Soetomo General Hospital, Indonesia. Methods: This retrospective cross-sectional study was performed by reviewing medical record of constipated children under 5 years of age at dr. Soetomo General Hospital Surabaya from January to December 2021. Data regarding age, gender, living place, body anthropometric (weight, height and nutritional status), sign and symptoms, and physical examination were collected for each patient. Nutritional status was determined by using WHO 2006 growth chart. We also assessed the presence of concomitant disease among those children and presented the data on the table. Results: A total of 35 subjects with constipation were included in this study. Mean (±SD) for age, body weight, length/height of these subjects were 27.09±17.71 months, 10.93±6.11 kg, 82.34±18.52 cm, respectively, with the male and female ratio of 1,67: 1. Around 18.2% of subjects presented with wasted, 18.2% with severely wasted, and 18.2% with severely stunted. Hardened stool (80%) was the most prevalent symptom, followed by straining (37.1%) and fecal impaction (22.9%). The most common concomitant diseases of childhood constipation were Hirschsprung’s disease (17.1%), congenital heart disease (11.4%), and hypothyroidism (11.4%). Conclusion: The results of this study showed that boys had a higher prevalence of constipation in children under 5 years of age, with the most prevalent clinical features being hardened stool, straining, and fecal impaction. Meanwhile, Hirschsprung’s disease, hypothyroidism, and congenital heart disease were the most concomitant disease.